THE ROLE OF VILNA IN THE RENAISSANCE OF BELARUSIAN PRESS IN THE EARLY 20TH CENTURY: IDEOLOGICAL AND PERSONAL RELATIONS - DOVNAR, LARISA (Knygotyra, 2015)
The role of Vilna as the general cultural area in the genesis of the national form of the Belarusian book culture is analysed. The way of forming the national self-consciousness, the national idea of the Belarusians in the sphere of the dominating types of culture (Polish, Russian), different political tendencies in which the most important part was played by national print are retraced.Attention is focused on the development of periodical press in Belarusian in the early 20th century (“Nasha Dolia”, “Nasha Niva”) in the multinational Vilna area. First of all, there are displayed the Belarusian–Lithuanian idea and personal intercommunications which are confirmed by publishing activities. The author concludes that Vilna was the place of the Renaissance of the Belarusian national print which became a unique phenomenon of nobilitation of the Belarusian language, literature, book and the Belarusian nation.
Keywords: ...